The Finnish telecom sector facing next generation standards: Indigenous capabilities versus R&D alliances - Christopher Palmberg; Olli Martikainen (The Research Institute of the Finnish Economy (ETLA), 2004)
After the success related to the GSM standard, the Finnish telecom sector has come to the crossroads and now phases various possible paths to follow and challenges to master. At present there is technological and market competition both within and between different next generation telecom standards. Against this background we identify three possible future scenarios of these next generation standards, and analyse recent patterns of internal and external diversification of prominent Finnish telecom firms using data on patents and strategic R&D alliances. Our results indicate that the Finnish telecom sector has diversified its technological base in recent years. The sector appears internally/indigenously weak in Internet-related new telecom technology fields and related applications. However, telecom firms have also extensively engaged themselves in complementary R&D alliances in these fields. We assess the limitations, present and possible future implications of these findings. – – GSM-standardin luoman menestyksen jälkeen suomalainen tietoliikenneala on uusien valintojen ja haasteiden edessä. Tällä hetkellä on käynnissä kilpailu useiden seuraavan sukupolven teknologiastandardien välillä, sekä siitä mihin standardeihin nykyiset markkinat siirtyvät. Tätä taustaa vasten identifioimme kolme mahdollista skenaariota seuraavan sukupolven standardien valinnalle. Lisäksi analysoimme merkittävimpien suomalaisten tietoliikennealan yritysten sisäistä ja ulkoista diversifikaatiota lähihistoriassa käyttäen tietoja patenteista ja strategisista T&K alliansseista. Tutkimuksen perusteella suomalainen teleala on hajauttanut teknologiapohjaansa viime vuosien aikana. Vaikuttaa myös siltä, että sisäiset teknologiapanostukset uusiin Internetpohjaisiin tietoliikenneratkaisuihin ja sovelluksiin ovat olleet vähäisempiä kuin traditionaalisille alueille. Näille uusille alueille on kuitenkin käynnistetty runsaasti komplementaarisia T&K-alliansseja. Arvioimme näiden havaintojen tämänhetkistä ja tulevaa merkitystä sekä niiden mahdollisesti aiheuttamia rajoitteita.
Keywords: 330; Standards; Finnish telecom; diversification; R&D alliances; Standardit; Suomen tietoliikenneala; diversifikaatio; T&K-allianssit; Finnland; Telekommunikationsgesellschaft; Industrielle Forschung; Normung; Unternehmenskooperation